PENGARUH CITRA NEGARA ASAL DAN PERSEPSI KUALITAS TERHADAP LOYALITAS MEREK STUDI PADA KONSUMEN PESAWAT TELEVISI LG DI KOTA PONTIANAK - PURNAMA B11110032, NOVA BUDI (Jurnal Manajemen Update, 2014)
This research was motivated by the increasing competition in the marketing of electronic products in countries where Indonesia is a potential market as the country's international trade objectives. This phenomenon makes foreign and domestic companies have to have a specific strategy to attract consumers that are loyal to their products. To increase loyalty there are several ways of creating a good image of the country as the country of origin of the goods-producing and improving the quality of their products. This study aims to analyze the influence of the image of the country of origin, and perceived quality on brand loyalty in the LG television at Pontianak city. This study was conducted using quantitative causal form. In this study the distribution of questionnaires to 100 users LG television at Pontianak city using snawball sampling technique, after the analysis of data obtained by using quantitative data analysis. Quantitative analysis includes: Test Validity and Reliability, Testing Assumptions Classic, Multiple Regression Analysis, hypothesis testing via t-test and F-test, and analysis of the coefficient of determination (R2). From the results of this study indicate that the image of the country of origin and perceived quality individually and jointly significant effect on brand loyalty in products LG television at Pontianak city. From the test results can partially be seen that the perceived quality of the most dominant effect on brand loyalty in products LG television at Pontianak city. Keywords: brand loyalty, country of origin image, Perceived quality